ENTREPRENEURIAL COMPETENCE, ORIENTATION AND PRODUCT INNOVATION: DRIVERS OF MSMEs SUCCESS IN OK OCE INDONESIA - Nugraha, Muh Faqih Ikhwan Aditiya; Wibowo, Agus; Suparno (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to analyze the influence of competence and entrepreneurship on business success, with product innovation as a mediating variable, in micro, small, and medium enterprises (MSMEs) assisted by OK OCE Indonesia in the DKI Jakarta region. A quantitative approach was used, collecting data through questionnaires distributed to 150 MSMEs selected through purposive sampling. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS 3.0 software. The results showed that competence and entrepreneurship have a positive and significant effect on business success. Both variables also have a significant contribution to product innovation, which is further proven to have a positive effect on business success. Product innovation has been shown to act as a mediator, although the resulting mediation effect is relatively limited. The practical implications of this study can be the basis for the development of more targeted training, mentoring, and capacity building programs to support the effectiveness of MSME empowerment programs by OK OCE.